2021
DOI: 10.3390/ijerph18073628
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunctional Customer Behavior, Employee Service Sabotage, and Sustainability: Can Social Support Make a Difference?

Abstract: In a restaurant industry, dysfunctional customer behavior damages customer-contact service employees’ mental health which may lead to employee defection. This study examined the effects of dysfunctional customer behavior on service employees’ service sabotage which is a mechanisms for protecting themselves from outside pressures. Additionally, it determined if emotional exhaustion plays a mediating role in the relationship between dysfunctional customer behavior and employees’ service sabotage and verified the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 83 publications
0
8
0
Order By: Relevance
“…Third, what had received little attention to the boundary conditions under which DCB exerts more or less detrimental effects on employee emotional labor. Perceived organizational support has been shown to moderate the effects of DCB on employees’ wellbeing and behaviors, such as burnout ( Han et al, 2016 ), employee service sabotage ( Hwang et al, 2021 ), and job anxiety ( Raza et al, 2021 ). Our study demonstrated that POS (as external resources) and customer orientation (as internal resources) attenuate the effects of different types of DCB on emotional labor of frontline employees, provided a better understanding of the mechanism underlying the influence, and contributed to the previous literature.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Third, what had received little attention to the boundary conditions under which DCB exerts more or less detrimental effects on employee emotional labor. Perceived organizational support has been shown to moderate the effects of DCB on employees’ wellbeing and behaviors, such as burnout ( Han et al, 2016 ), employee service sabotage ( Hwang et al, 2021 ), and job anxiety ( Raza et al, 2021 ). Our study demonstrated that POS (as external resources) and customer orientation (as internal resources) attenuate the effects of different types of DCB on emotional labor of frontline employees, provided a better understanding of the mechanism underlying the influence, and contributed to the previous literature.…”
Section: Discussionmentioning
confidence: 99%
“… Szczygiel and Bazińska (2021) further state that customer incivility’s effect on emotional exhaustion is mediated by surface acting and moderated by emotional intelligence. In addition, customer incivility’s also is a predictor of employees’ behavior such as retaliatory behaviors ( Gong and Wang, 2019 ), sabotage service ( Hwang et al, 2021 ), and turnover ( Bamfo et al, 2018 ). However, the negative factors of customers (e.g., customer verbal abuse, illegitimate complaint, disproportionate demand) are generally believed to be difficult to manage by the service firms.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Frontline service employees are often faced with a variety of unpredictable situations, which correspond to stressors, from which they are prone to experience emotional disorders or exhaustion in the workplace. This can adversely affect employee physical and mental health ( Hwang et al, 2021 ). Therefore, dysfunctional customer behaviors are one of the key predictors driving frontline service employee sabotage action ( Yagil, 2021 ), such as joking about customers or colleagues to please themselves, neglecting to comply with company rules and regulations, adjusting the speed of service according to one’s own emotions or personal needs, expressing hostility, anger, or frustration to customers, deliberately delaying service depending on employees’ moods and emotions, deliberately making inappropriate remarks or responses to customers, retaliating against customers in a rude manner, etc.…”
Section: Research Framework and Hypothesesmentioning
confidence: 99%